The Effects of the Opticals Properties on the (PMMA) Puerty - Rashid, K. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research, we studied the effect of (Î²-rays) on the optical properties of pure (PMMA) films prepared by using casting technique, and the optical properties for these films was studied before and after irradiation by recording the Absorption and Transmission spectra for a range of wavelength range (190-1100) nm. and then the absorption and Transmission and the reflectivity, extinction coefficient, refractive index, and real and imaginary parts of dielectric constant was studied